Cost-benefit analysis of energy efficiency system for homes and buildings - Chen, Lue (2014)
This report is to summarize the process of designing the cost-benefit analysis model and development the software Energy Management System. It will start with the introduction of the project, which includes the background as well as the objectives and scope. After this, a literature review will be included. There are two main modules which will be introduced in the report to evaluate the feasible cost reduction. Eight different types of electrical facilities will be used to do the cost-benefit analysis. Two case studies for the two main modules will be used to prove the usability and accuracy of the Energy Management System. At last, a conclusion will be drawn with the recommendations to improve the software. Meanwhile, the learning experience throughout the whole project will also be shown.